2022
DOI: 10.3390/s22020513
|View full text |Cite
|
Sign up to set email alerts
|

Let the Cat out of the Bag: Popular Android IoT Apps under Security Scrutiny

Abstract: The impact that IoT technologies have on our everyday life is indisputable. Wearables, smart appliances, lighting, security controls, and others make our life simpler and more comfortable. For the sake of easy monitoring and administration, such devices are typically accompanied by smartphone apps, which are becoming increasingly popular, and sometimes are even required to operate the device. Nevertheless, the use of such apps may indirectly magnify the attack surface of the IoT device itself and expose the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Chatzoglou et al in their work [37] examined more than forty IoT based Android official apps statically and dynamically and found that majority of the apps have a range of security and privacy issues. There were repeated incidents of malicious code injection into popular Android apps through advertising SDKs, as in the case of CamScanner in 2021 [?].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chatzoglou et al in their work [37] examined more than forty IoT based Android official apps statically and dynamically and found that majority of the apps have a range of security and privacy issues. There were repeated incidents of malicious code injection into popular Android apps through advertising SDKs, as in the case of CamScanner in 2021 [?].…”
Section: Discussionmentioning
confidence: 99%
“…Section II is the overview of the work done, section III is the preliminary study, section IV is the proposed method, section V is evaluation, section VI is related works, and section VII is conclusion. Chatzoglou et al in their recent work [37] closely examined more than forty top Android official apps belonging to six Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…The Internet of Things has revolutionized the way data are connected and transformed between physical and virtual entities. Traditional IoT systems, operating on centralized architectures, face challenges like single points of failure and concerns regarding the security, transparency, privacy, integrity, and confidentiality of data [47,127,128]. These challenges have the potential to hinder the future development and application of IoT technology.…”
Section: Iot Applicationsmentioning
confidence: 99%
“…Chatzoglou et al [17] use existing tools and frameworks to analyze the security of IoT companion apps. Their study finds existing CWEs, third-party trackers and some other known issues in the companion apps.…”
Section: Related Workmentioning
confidence: 99%